Raising Our Children To Be Resilient : a Guide To Helping Children Cope With Trauma In Today's World. - Goldman, Linda (Taylor & Francis Ltd., 2004)
Today's omnipresent media means children cannot avoid a constant stream of images and accounts of frightening events around the world. This book is designed to to help children through their pain and confusion and guide them into a flexible and.